10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Objective To determine the prevalence and clinical characteristics of patients with "low-positive" (LP) MOG-IgG (titres 1:160-1:320) among adults with a first demyelinating event (FDE) suggestive of multiple sclerosis (MS). Methods From the Barcelona CIS inception cohort, we included adult patients with serum collected ≤ 6 months from the FDE. MOG-IgG was assessed by a cell-based assay with flow cytometry (CBA-FC). Demographic, clinical, and paraclinical data were compared among seronegative, LP, and "clear-positive" (CP; ≥ 1:640) patients. Supporting MOGAD features and final diagnoses were retrospectively reviewed in seropositive cases. Results Of 613 patients, 42 (6.9%) were MOG-IgG positive (CP = 17; LP = 25). LP patients were indistinguishable from seronegative patients but differed from CP patients, who more frequently had optic neuritis, lacked cerebrospinal fluid-oligoclonal bands, and were less likely to meet the McDonald criteria (p < 0.05). At the last follow-up, 64% of LP versus 18% of CP patients were diagnosed with MS (p = 0.004). Only one LP patient fulfilled MOGAD criteria, compared with 14 CP patients (p < 0.001). Interpretation Lowering the CBA-FC positivity threshold to ≥ 1:160 had limited diagnostic yield in this MS-predominant cohort, as most LP cases were ultimately diagnosed with MS. These findings support cautious interpretation of LP MOG-IgG results in this clinical setting.